Pengaruh Kualitas Produk terhadap Kepuasan Konsumen di Usaha Kipang Sisera Panyabungan Kabupaten Mandailing Natal - Regina May Putri; Andi Hakim; Rizka Ar-Rahma (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
This study aims to analyze the effect of product quality on consumer satisfaction at Kipang Sisera Panyabungan Business. The research method used is a quantitative approach with data collection techniques through observation, interviews, and distributing questionnaires to 96 respondents who are Kipang Sisera customers. The data obtained were analyzed using validity, reliability, and regression analysis tests with the help of SPSS 25. The results of the validity test showed that all items in the questionnaire were valid with a calculated r value> r table (0.1689), while the results of the reliability test using Alpha Cronbach showed a value> 0.60, which means that the research instrument can be trusted. The results of the partial regression test (t test) showed that product quality had a positive and significant effect on consumer satisfaction with a significance value of 0.000 <0.05. The coefficient of determination (R²) test showed that product quality contributed 62.9% to consumer satisfaction, while the rest was influenced by other variables not examined in this study.